El Fondo Nacional de Desarrollo Regional: un análisis descriptivo - García, Bernardita (Revista EURE - Revista de Estudios Urbano Regionales, 1985)
The author analizes the administrative, legislative and budgeting aspects related with the National Fund for Regional Development FNDR. She also examines the most important figures datin from the period 1976-1982 and verifies the decreasing trend in the importance of this Fund. Changes in interregional Fund allocation are significant and contradict the official regional development priorities. Í